Identifying Thresholds for Similarity-Based Class Cohesion (SCC) Metrics - Pradana, Fajar; Priyambadha, Bayu; Rusdianto, Denny Sagita (Journal of Information Technology and Computer Science, 2016)
Abstract. The object-oriented design (OOD) concept can be used to implement a quality measurement program is based on the possibility of inter-relationship between attributes and methods in the class diagram and interaction between objects on a communication diagram. The process of calculating the value of cohesion on the design of object-oriented software using Similarity-Based Class Cohesion metrics can be done by identifying the relationship between the three types of possible interaction between those methods, method-attribute, and interaction attribute-attribute. But the existence of such measurements theory is rarely used in the software development industry. This is due to there is no threshold value that is used as the limit of good or bad design. This study aims to determine the threshold of cohesion metric based on the class diagram. The result showed that the threshold of SCC metric is 0.45. 0.45 is the value that has the highest level of agreement with the design expert